Psychometric Evaluation of the Disaster Preparedness Evaluation Tool© (DPET) on Emergency Nurses in Mainland China: Two Cross-Sectional Studies. (5th June 2022) - Wang, Jia; Lu, Sihui; Sun, Xinglan; Wang, Fen; Wan, Meijuan; Chen, Hanxi; Tan, Yibing
Abstract: Background: Emergency nurses play a major role in disaster relief in mainland China, but there is no valid instrument to measure the extent of their disaster preparedness. The Disaster Preparedness Evaluation Tool © is a reliable instrument to assess the disaster preparedness of nurse practitioners. The tool has been translated and validated in Saudi Arabia, Taiwan, China and the United States of America. Objectives: This study aimed at translating and adapting the Disaster Preparedness Evaluation Tool © (DPET) for emergency nurses in mainland China and determining its psychometric properties. Design, Settings and Participants: A total of 2 cross-sectional online surveys were conducted in the emergency departments of 26 public grade III-A hospitals in Guangdong, mainland China. In the first study, 633 emergency nurses were recruited from May to August, 2018. In the second study, 205 were recruited in April 2019. Methods: The instrument was adapted through rigorous forward-backward translation, face validity, and pre-test processes. Exploratory factor and parallel analyses were used in the first study. Confirmatory factor analysis, internal consistency and split-half reliability were used in the second study. Results: Exploratory factor and parallel analyses extracted a 5-factor solution comprising of 34 items that accounted for 64.06% of the total variance. The fit indices indicated a good model fit. The reliability was good, as indicated by a Cronbach's alpha of 0.97 and a split-half reliability coefficient of 0.97. Conclusion: The mainland China version of the DPET (DPET-MC) was a reliable and valid instrument and can be used in practice.